2023
DOI: 10.21037/apm-22-435
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean section complicated with presumed massive pulmonary embolism and cardiac arrest treated with rescue thrombolytic therapy—two case reports

Abstract: Background: Massive pulmonary embolus (PE), resulting in cardiac arrest during pregnancy and postpartum, is a rare but potentially catastrophic event. The most severe manifestation of massive PE is cardiovascular instability, including cardiogenic shock and cardiac arrest requiring intensive care unit (ICU) admissions. Up to 23% of high-risk PE pregnant and postpartum patients experience cardiac arrest.Case Description: Case 1, a 34-year-old obese patient, with a twin pregnancy, had cesarean sections in the 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Numerous studies have consistently reported favourable thrombolysis outcomes when managing patients with CA, particularly CAs possibly caused by a pulmonary embolism [16,24,25]. However, bleeding complications associated with this treatment modality are relatively high [17,24]. Consequently, thrombolysis cannot be a routine CA intervention in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have consistently reported favourable thrombolysis outcomes when managing patients with CA, particularly CAs possibly caused by a pulmonary embolism [16,24,25]. However, bleeding complications associated with this treatment modality are relatively high [17,24]. Consequently, thrombolysis cannot be a routine CA intervention in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This can3 be achieved by using either mechanical or pharmacological methods. Starting patients on anticoagulation early in case of suspected PE may be lifesaving and crucial to prevent catastrophic sequalae [6]. The diagnosis of suspected PE includes compression lower limbs ultrasound in case of signs and symptoms of deep vein thrombosis (DVT).…”
Section: Discussionmentioning
confidence: 99%
“…This case involves a 34-year-old obese parturient with twin pregnancy undergoing CD due to premature abruption of the placenta. She experienced sudden cardiac arrest immediately after birth and although she was successfully treated with heparin and rt-PA, she underwent rescue hysterectomy soon after ROSC (18). In general, VTE associated mortality rates in the peripartum period are low, though higher that the non-obstetric population (8).…”
Section: Discussionmentioning
confidence: 99%